Combustion particulate emissions in Africa: regional climate modeling and validation - (:unkn) unknown (My University, 2008)
Africa, as a major aerosol source in the world, plays a key role in regional and global geochemical cycles and climate change. Combustion carbonaceous particles, central in this context through their radiative and hygroscopic properties, require ad hoc emission inventories. These inventories must incorporate fossil fuels FF (industries, traffic,...), biofuels BF (charcoal, wood burning,... quite common in Africa for domestic use), and biomass burning BB regularly occurring over vast areas all over the African continent. This latter, subject to rapid massive demographic, migratory, industrial and socio-economic changes, requires continuous emission inventories updating, so as to keep pace with this evolution. Two such different inventories, L96 and L06 with main focus on BB emissions, have been implemented for comparison within the regional climate model RegCM3 endowed with a specialized carbonaceous aerosol module. Resulting modeled black carbon BC and organic carbon OC fields have been compared to past and present composite data set available in Africa. This data set includes measurements from intensive field campaigns (EXPRESSO 1996, SAFARI 2000), from the IDAF/DEBITS surface network and from MODIS, focused on selected west, central and southern African sub-domains. This composite approach has been adopted to take advantage of possible combinations between satellite high-resolution coverage of Africa, regional modeling, use of an established surface network, together with the patchy detailed knowledge issued from past short intensive regional field experiments. Stemming from these particular comparisons, one prominent conclusion is the need for continuous detailed time and spatial updating of combustion emission inventories apt to reflect the rapid transformations of the African continent.
Keywords: African Research